Development of smartphone-based student attendance system - Islam, Md. Milon; Hasan, Md. Kamrul; Billah, Md Masum; Uddin, Md. Manik (2017 IEEE Region 10 Humanitarian Technology Conference (R10-HTC), 2017)
Student's attendance tracking is a vital issue in order to monitor students' performance in the classroom as well as in their studies. It becomes a key concern because the university authority maintains a rule that one student can only attend in the exam if his/her attendance is higher or equal to several percentages (60%,70% or 80% etc.) otherwise not. The traditional attendance system needs student's to physically sign the attendance sheet each time for the attendance of each class. This is unnecessarily time-consuming to notice and mark student's name on the attendance sheet. This also happens that some students may accidentally or willingly mark the student's name like as proxy. The hard copy of attendance sheet may get lost. Using Smartphone like as Android Technology the course teacher will be able to take attendance easily by our designed mobile application and save the attendance in the phone as well as in server and can check percentage and also can print as hard copy. Using the stored information, this system is able to mark attendance, marking intruders' entry, attendance percentage calculations, send emails, and send SMS to the guardian to keep them updated about their child's attendance at the Institute. The designed system has an online access from any place and any moment which may extraordinarily assist the course teacher with keeping track of their student's attendance.